Motivation Among Workers In A Semiconductor Manufacturing Company In Melaka, Malaysia: An Exploratory Study. - Ong , Ming Seng (2010)
The study aimed to provide insight for the management of the company to retain employees. The independent variables of study included salary, recognition, affiliation, security, work itself, advancement and achievement. In the study five moderating variables were introduced, namely gender, age, job position, ethnic and educational level. The dependent variable for the study was motivation.The respondents were based on sampling. A total of 191 respondents across segments and support functions participated in this research.